Kontribusi Daya Tarik Wisata Pantai Melasti Terhadap Sosial Ekonomi Masyarakat Lokal Di Desa Ungasan, Kecamatan Kuta Selatan - Romer, Krista Sisilia; Sugiarti, Dian Pramita (JURNAL DESTINASI PARIWISATA, 2023)
This research aims to discover the socio-economic contribution of Melasti Beach to the local community of Ungasan Village. This research was conducted at Melasti Beach, Ungasan Village, South Kuta District, Badung Regency. The scopes of this research are the involvement of the local community and the socio-economic contribution. Data collection techniques used in this research included observation, interview, and documentary methods. The technique of informant determination used is purposive sampling. A descriptive qualitative method is used to analyze the data. The stages of data analysis commenced with data collection, subsequently data reduction, data display, and conclusion drawing/ verification. The study uncovered that the presence of Melasti Beach results in various benefits to the socioeconomic life of the local community in Ungasan Village. Melasti Beach contributes to the local community by providing new job dan business opportunities, increasing income, escalating locals’ prosperity, and family education investment. To maximize the socio-economic contribution of Melasti Beach, the management is required to intensify local community involvement by striving to vary more job and business opportunitiesfor the locals in every possible way. Keywords: Local community, Contribution, Socio-Economic